Fabrication of magnetic molecularly imprinted polymer-based covalent–noncovalent synergistic imprinting strategies for the highly specific enrichment of luteolin from honeysuckle - Zhang, Liping; Hao, Peizhi; He, Yifan; Li, Shujing; Li, Tian; Wang, Lan; He, Suna (Frontiers in Sustainable Food Systems, 2024)
A novel surface imprinting polymer for luteolin, denoted as Fe3O4@SiO2@MIP, was synthesized using covalent-noncovalent synergistic imprinting strategies. In this system, 3-acrylamidephenylboric acid was adopted as covalent functional monomer, deep eutectic solvent (choline chloride/methacrylic acid (ChCl/MAA, 1/2, n/n)) and methacrylic acid as the non-covalent functional monomers, and Fe3O4@SiO2 nanoparticles as the magnetic support. The resultant Fe3O4@SiO2@MIP displayed a uniform morphology, good crystallinity, and excellent magnetic properties. Meanwhile, the binding experiments demonstrated that Fe3O4@SiO2@MIP exhibited high binding performance and the maximum adsorption capacity was 20.97 mg/g. Moreover, Fe3O4@SiO2@MIP also exhibited excellent selectivity and reusability behavior. In addition, this polymer, serving as an adsorbent, presented practical application potential in separation and enrichment of LTL from honeysuckle. The innovative research provided a new strategy for the enrichment of LTL in complex samples, contributing to a theoretical basis for the quality control of honeysuckle.